Social orderings for the assignment of indivisible objects. - Maniquet, François (Journal of Economic Theory, 2008)
In the assignment problem of indivisible objects with money, we study social ordering functions which satisfy the requirement that social orderings should be independent of changes in preferences over infeasible bundles. We combine this axiom with efficiency, consistency and equity axioms. Our result is that the only social ordering function satisfying those axioms is the leximin function in money utility. Copyright (c) 2008 Elsevier Inc.